The Role of Resilience and Self-Awareness on Quarter Life Crisis in Generation Z Workers - Puspaningrum, Sari Dewi; Qatrunnada, Rizqi Zulfa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to examine how resilience and self-awareness affect quarter life crisis in generation Z workers. The population in this study were workers with the characteristics of generation Z who were born in 1997-2012, aged 20-28 years, male and female and at least 1 year of work. The sampling technique used is non-probality sampling. The sample in this study used purposive sampling. This research method is quantitative method. The data collection technique uses a quarter life crisis scale, resilience, and self-awareness with a questionnaire designed using a Likert scale. Data analysis was conducted using multiple linear regression techniques to test the hypothesis. The results showed that resilience and self-awareness had a significant effect on quarter life crisis, with a significance value of F = 599.237, R = 0.895, and p = 0.000 (sig < 0.05). Resilience has a significant negative relationship with quarter life crisis with an effective contribution of 80.1%, while self-awareness shows a significant positive relationship but with a very small contribution, which is 0.0019%. Thus, it is concluded that there is a significant relationship between resilience and self-awareness on quarter life crisis in generation Z workers, with resilience playing a more dominant role.